Flow and Turbulence Due To Wood Contribute to Declogging of Gravel Bed - I. Schalko; M. Ponce; S. Lassar; S. Schwindt; S. Haun; H. Nepf (Geophysical Research Letters)
Abstract The placement of wood in rivers is a common restoration method used to locally affect hydraulic and morphologic conditions to create habitat. Laboratory experiments demonstrated that wood placements can also promote surface declogging, that is, removal of fine sediment from a gravel bed, thereby restoring spawning grounds for fish. Logs of different size and submergence level were placed on a gravel bed clogged with fines. Surface declogging was observed in regions of elevated turbulence in the log wake and elevated velocity adjacent to the log. A criteria for declogging was identified based on a modified non‐dimensional Shields parameter combining mean and turbulent velocity at the bed. The footprint of declogged bed scaled with log dimensions. Emergent logs produced a larger declogging footprint compared to submerged logs of the same length, due to their stronger influence on the flow field. Logs were also shown to prevent clogging over similar areas.